Implanting Character Values Based On Local Culture (Tabea Culture) At Early Childhood Education And Development (ECED) Telkom In Ternate Municipality - Achmad, Fatoni; Srinawati, Risna; Amaliah, Nur; Sultoni, Agus; Muin, Mulyanti (Jurnal Ilmiah Cahaya Paud, 2023)
The rapidly development of technology and globalization can negatively affect characters. It is therefore necessary to perform various efforts optimally to strengthen the early childhood’s characters. This research aimed to figure out the character values of local culture (Tabae culture) and how they were implanted at ECED Telkom in Ternate Municipality. The research used a qualitative approach. Its subjects were Class-B students and teachers at ECED Telkom in Ternate Municipality who had provided information to answer the problems discussed in this research. The research data were collected using several research instruments before they were descriptively analyzed. The research results showed that the character values based on local culture (Tabea culture) were implanted through learning, habituation, and exemplification. The character values found in local culture (Tabea culture) were reflected in their attitudes, such as being respectful and polite, loving and caring, kind and humble, as well as tolerant and peace-loving.